ÎNVĂŢĂMÂNT ELECTRONIC DESCHIS LA DISTANŢĂ: REPERE DE ORGANIZARE ŞI FUNCŢIONARE - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Umanistice, 2007)
The purpose of the present work is forming a generalized and integral representation about education and distance learning; about features, opportunities, freedom and advantages of the Open Distance Electronic Learning in comparison with traditional forms. The awareness of these things will promote the best understanding of processes of the distance learning by means of modern information and telecommunication technologies, and also to a substantiation of a choice of didactic strategy ODL. I hope also that this work will arouse a big interest and heightened attention from the part of chiefs of the educational units concerning questions of reforming of the educational system with the help of more resolute integration of calculating and telecommunicating means during learning and education.